2021
DOI: 10.1017/ehs.2021.7
|View full text |Cite
|
Sign up to set email alerts
|

Children and innovation: play, play objects and object play in cultural evolution

Abstract: Cultural evolutionary theory conceptualises culture as an information-transmission system whose dynamics take on evolutionary properties. Within this framework, however, innovation has been likened to random mutations, reducing its occurrence to chance or fortuitous transmission error. In introducing the special collection on children and innovation, we here place object play and play objectsespecially functional miniaturesfrom carefully chosen archaeological contexts in a niche construction perspective. Given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 124 publications
0
24
0
Order By: Relevance
“…For example, in a meta-ethnographic review of studies examining how hunter-gatherer children acquire subsistence skills, Lew-Levy and her colleagues (2017) reported that it is not until adolescence before adults begin to directly teach children complex skills such as tool manufacture and hunting. Adults in traditional and hunter-gatherer societies do, however, engage in what could be described as indirect teaching of children, as reflected by storytelling around evening fires or providing children with toy tools to use in their play, which contribute to children's acquisition of important skills and knowledge (e.g., Lew-Levy et al, 2017;Nowell, 2021;Riede et al, 2018Riede et al, , 2021. Regardless if we focus on teaching or imitation, children develop remarkable social-learning abilities over the preschool years, with social learning being the principal mechanism responsible for Homo sapiens' expansive material and intellectual culture (Legare, 2019;Tomasello, 2019).…”
Section: Children's Remarkable Social-learning Abilitiesmentioning
confidence: 99%
“…For example, in a meta-ethnographic review of studies examining how hunter-gatherer children acquire subsistence skills, Lew-Levy and her colleagues (2017) reported that it is not until adolescence before adults begin to directly teach children complex skills such as tool manufacture and hunting. Adults in traditional and hunter-gatherer societies do, however, engage in what could be described as indirect teaching of children, as reflected by storytelling around evening fires or providing children with toy tools to use in their play, which contribute to children's acquisition of important skills and knowledge (e.g., Lew-Levy et al, 2017;Nowell, 2021;Riede et al, 2018Riede et al, , 2021. Regardless if we focus on teaching or imitation, children develop remarkable social-learning abilities over the preschool years, with social learning being the principal mechanism responsible for Homo sapiens' expansive material and intellectual culture (Legare, 2019;Tomasello, 2019).…”
Section: Children's Remarkable Social-learning Abilitiesmentioning
confidence: 99%
“…At the same time, however, the topic remains poorly heeded in archaeological pedagogy (Lyman, 2021). Given that cultural evolutionary theory itself teaches us that aspects of culture most easily and rapidly change when scaffolded through active teaching (Riede et al, 2021), we recommend that, after half a century, Dunnell's Systematics in prehistory – and with it rigorous and replicable ways of classifying material culture – are placed more abundantly on our curricula, in addition to continuing the ongoing critique and transformation of existing classifications through novel research. Only when the construction and meaning of our analytical units and their relationships among one another are transparent and robust cultural taxonomies are in place can we seriously hope to understand the patterns and processes that have shaped cultural evolution in deep history.…”
Section: Systematics In Prehistory and The Emergence Of Evolutionary ...mentioning
confidence: 99%
“…It is especially important to start applying innovations in the educational process of preschool education, as the modernization of the preschool education system, its current development requires effective methodological management of the process of implementation of pedagogical innovations in practice to improve the quality of educational services [11,17]. The educational process in PEI should be carried out according to the formula: "implementation of innovations = correspondence to the requirements of the time and social demands + vector of progress in the implementation of educational aims".…”
Section: The Analysis Of the Recent Publications On The Essence Of In...mentioning
confidence: 99%